2014
DOI: 10.1109/tvcg.2014.2346431
|View full text |Cite
|
Sign up to set email alerts
|

Overview: The Design, Adoption, and Analysis of a Visual Document Mining Tool for Investigative Journalists

Abstract: For an investigative journalist, a large collection of documents obtained from a Freedom of Information Act request or a leak is both a blessing and a curse: such material may contain multiple newsworthy stories, but it can be difficult and time consuming to find relevant documents. Standard text search is useful, but even if the search target is known it may not be possible to formulate an effective query. In addition, summarization is an important non-search task. We present Overview, an application for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 30 publications
0
62
0
2
Order By: Relevance
“…This strategy has been extensively discussed in the visualization community to facilitate investigative analysis [45,53], the exploration of news articles [11], book collections [46], and artworks [21]. Studies have shown that the strategy of coordinated views is useful for the analysis of large and complex document collections, both in professional [5,18] and casual contexts [11,21]. Thudt et al highlight this strategy as particularly effective for supporting open-ended exploration and serendipitous discoveries [46].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…This strategy has been extensively discussed in the visualization community to facilitate investigative analysis [45,53], the exploration of news articles [11], book collections [46], and artworks [21]. Studies have shown that the strategy of coordinated views is useful for the analysis of large and complex document collections, both in professional [5,18] and casual contexts [11,21]. Thudt et al highlight this strategy as particularly effective for supporting open-ended exploration and serendipitous discoveries [46].…”
Section: Related Workmentioning
confidence: 99%
“…Meanwhile in the visualization community long-term research processes and outcomes supported by visualization have been discussed in the area of journalism [5] and in casual scenarios [21]. What we lack are in-depth and long-term studies that show how information visualization can facilitate humanities research processes and how such visualizations integrate into traditional approaches such as archival work and close reading.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Il s'applique à des matrices binaires pour identifier des blocs dont les cellules sont uniquement composées de 1 (Figure 2b (Figure 4). En effet, l'exploration hiérarchique des sujets est plus efficace qu'une exploration plate basée sur des listes [16] et préférée par les journalistes utilisant Overview [7].…”
Section: Extraction Des Variantes De Sujetunclassified